Malignant peripheral nerve sheath tumors in children, adolescents, and young adults: Treatment results of five Cooperative Weichteilsarkom Studiengruppe (CWS) trials and one registry. Issue 7 (18th August 2020) - Meister, Michael T.; Scheer, Monika; Hallmen, Erika; Stegmaier, Sabine; Vokuhl, Christian; von Kalle, Thekla; Fuchs, Jörg; Münter, Marc; Niggli, Felix; Ladenstein, Ruth; Kazanowska, Bernarda; Ljungman, Gustaf; et al.
Abstract: Background and Objectives: Malignant peripheral nerve sheath tumors (MPNST) are aggressive soft tissue sarcomas that present as large, invasive tumors. Our aim was to assess outcomes, identify prognostic factors, and analyze treatment strategies in a prospectively collected pediatric cohort. Methods: Patients less than 21 years with MPNST treated in the consecutive prospective European Cooperative Weichteilsarkom Studiengruppe (CWS)‐trials (1981‐2009) and the CWS‐SoTiSaR registry (2009‐2015) were analyzed. Results: A total of 159 patients were analyzed. Neurofibromatosis type I (NF1) was reported in thirty‐eight patients (24%). Most were adolescents (67%) with large (>10 cm, 65%) tumors located at extremities (42%). Nodal involvement was documented in 15 (9%) and distant metastases in 15 (9%) upon diagnosis. Overall, event‐free survival (EFS) was 40.5% at 5 and 36.3% at 10 years, and overall survival (OS) was 54.6% at 5 and 47.1% at 10 years. Age, NF1 status, tumor site, tumor size, Intergroup Rhabdomyosarcoma Study (IRS) group, metastatic disease, and achieving first complete remission (CR1) were identified as prognostic factors for EFS and/or OS in the univariate analysis. Conclusions: Prognostic factors were identified and research questions for future clinical trials were addressed.